Demographic Profile of Older Adults Using Wheeled Mobility Devices - Amol M. Karmarkar; Brad E. Dicianno; Rosemarie Cooper; Diane M. Collins; Judith T. Matthews; Alicia Koontz; Emily E. Teodorski; Rory A. Cooper (Journal of Aging Research)
The purpose of this study was to determine whether the use of wheeled mobility devices differed with respect to age, gender, residential setting, and health-related factors among older adults. A total of 723 adults ageing 60 and older are representing three cohorts, from nursing homes, the Center for Assistive Technology, and the wheelchair registry from the Human Engineering Research Laboratories. Wheeled mobility devices were classified into three main groups: manual wheelchairs, power wheelchairs, and scooters. Our results found factors including age, gender, diagnosis, and living settings to be associated with differences in use of manual versus powered mobility devices. Differences in use were also noted for subtypes of manual (depot, standard, and customized) and powered (scooter, standard, and customized) mobility devices, on demographic, living arrangements, and health-related factors. Consideration of demographic, health-related, and environmental factors during the prescription process may help clinicians identify the most appropriate mobility device for the user.